Measles surveillance activities in the Metropolitan Area of Milan during 2017-2018 - BIANCHI, S. (J Prev Med Hyg, 2019)
INTRODUCTION: In Italy, the transmission of measles is still endemic, and 7,919 cases were reported to the National Surveillance System between January 2017 and December 2018. Aim of this study is to report the results of the measles surveillance activities in the Metropolitan City of Milan from March 2017 to December 2018, and to evaluate the surveillance performance WHO indicators. METHODS: The Local Health Units (LHUs) carried out case investigations and collected specimens to send to the EpiSoMI Lab (Subnational Reference Laboratory, SRL) of the University of Milan for cases/outbreaks confirmation and genotyping performed according to the WHO Guidelines. RESULTS: Overall, 610 suspected measles cases were reported by the surveillance system of the Metropolitan City of Milan. A total of 439 out of 540 cases with adequate specimens were laboratory-confirmed by molecular and/or serological assays. Two-hundred and thirty-six cases were notified as sporadic and 203 as related to 94 outbreaks. The most confirmed cases were aged 15–39 years, almost all not vaccinated. Overall, 282 cases were genotype D8 and 118 genotype B3. The evaluation of a set of indicators to monitor the quality of surveillance activities demonstrated the proficiency of the EpiSoMI Lab. CONCLUSIONS: A well-done investigation of cases and outbreaks by the surveillance local system, in a timely manner, in order to notify and investigate suspected cases and to laboratory confirm or discard cases is fundamental to reduce morbidity, to prevent further virus transmission and to achieve measles elimination.